Connection Between Support Social Friend Peers with Subjective Well-Being in Street Children - Nirmala Yunita Halim; Suroso Suroso; Isrida Yul Arifiana (Austronesia Akademika, 2024)
This study aims to investigate the relationship between peer social support and subjective well-being among street children. Street children are particularly vulnerable to negative emotional and psychological effects due to their harsh living conditions. This research used a quantitative approach with a correlational method to analyze the data. The sample consisted of 100 street children aged 12-18 years, selected through accidental sampling. The data were collected using questionnaires, and the relationship between the two variables was analyzed using Spearman's Rho correlation analysis. The subjective well-being of participants was measured using the scale developed by Diener, while social support was measured using the Sarafino scale. The results of the analysis indicated a significant positive correlation (r = 0.797, p < 0.01) between peer social support and subjective well-being. This means that higher levels of peer social support are associated with higher levels of subjective well-being in street children. The findings suggest that social support from peers plays a crucial role in enhancing the emotional and psychological health of street children. The study concludes that fostering positive peer relationships can improve subjective well-being, highlighting the importance of peer support in the lives of street children. Future research could explore other variables that influence subjective well-being to deepen our understanding of this issue complated.